Challenges related to drilling further north in the Norwegian Arctic - Lars, Løkling (University of Stavanger, Norway, 2015)
Master's thesis in Petroleum engineering The world’s energy demands are increasing rapidly and the oil & gas industry is forced to search for new acreages for exploration and production. The Arctic is expected to contain a vast amount of the remaining undiscovered hydrocarbons on this planet, thus making it an attractive region that could be essential for securing energy supplies for the future. The Arctic is however regarded as the most challenging area on the Earth, due to its extremely harsh conditions. Remoteness, cold temperatures, ice, rapid change in weather and long periods of darkness are some of the main conditions that can be expected. In other words, the region will add numerous challenges to the drilling and production operations. Large distances, lack of infrastructure, severe ice conditions and communicational issues are only some of the challenges the industry will have to overcome. This master thesis will be focusing on the challenges related to drilling and production in the Arctic, and the available technology and knowledge that exist to overcome them. With this in mind, the challenges that are relevant for the Norwegian Arctic when moving further north. will be reviewed and discussed. The usefulness of different rig types for exploration and field developments in the arctic will be presented, along with some modified versions, which are specifically made for application in the Arctic. Ice management and overcoming the large distances seems the most challenging for the next step of exploratory drilling in ice-infested waters located in remote areas. The capacity and reliance on an adequate communicational system will also play a huge role of arctic operations. Cooperation might be the key to success, not only for overcoming the operational and technical challenges, but also to get the social acceptance, political support and to make operations economically feasible